Development of portable aerosol mobility spectrometer for personal and mobile aerosol measurement. Issue 11 (1st November 2016) - Kulkarni, Pramod; Qi, Chaolong; Fukushima, Nobuhiko
ABSTRACT: We describe development of a portable aerosol mobility spectrometer (PAMS) for size distribution measurement of submicrometer aerosol. The spectrometer is designed for use in personal or mobile aerosol characterization studies and measures approximately 22.5×22.5×15 cm and weighs about 4.5 kg including the battery. PAMS uses electrical mobility technique to measure number-weighted particle size distribution of aerosol in the 10–855 nm range. Aerosol particles are electrically charged using a dual-corona bipolar corona charger, followed by classification in a cylindrical miniature differential mobility analyzer. A condensation particle counter is used to detect and count particles. The mobility classifier was operated at an aerosol flow rate of 0.05 L/min, and at two different user-selectable sheath flows of 0.2 L/min (for wider size range 15–855 nm) and 0.4 L/min (for higher size resolution over the size range of 10.6–436 nm). The instrument was operated in voltage stepping mode to retrieve the size distribution in approximately 1–2 min. Sizing accuracy and resolution were probed and found to be within the 25% limit of NIOSH criterion for direct-reading instruments. Comparison of size distribution measurements from PAMS and other commercial mobility spectrometers showed good agreement. The instrument offers unique measurement capability for on-person or mobile size distribution measurement of ultrafine and nanoparticle aerosol.